Assessment of helicobacter pylori infection with serological testing which is a fast and non-invasive method - Belkıs ÜNSAL,; Kadir AKSÖZ,; F. ERCİYES,; Sadun KOŞAY, (Turkish Journal of Gastroenterology, 2020)
-